Réponses

2014-01-18T14:02:22+01:00
 \frac{ \sqrt{3} + \sqrt{2} }{10+4 \sqrt{6} } \\= \frac{ \sqrt{3} + \sqrt{2} }{10+4 \sqrt{6} }  \times  \frac{ 10-6 \sqrt{6} }{10-4 \sqrt{6} } \\ = \frac{ (\sqrt{3} + \sqrt{2}) (10 - 4 \sqrt{6}) }{10^2-16 \sqrt{6}^2 }\\ = \frac{ (10\sqrt{3}-4\sqrt{18} + 10\sqrt{2} - 8 \sqrt{3}) }{100-96}\\  = \frac{ (10\sqrt{3}-12\sqrt{2} + 10\sqrt{2} - 8 \sqrt{3}) }{4}\\ = \frac{ 2\sqrt{3}- 2\sqrt{2} }{4}\\ = \frac{ \sqrt{3}- \sqrt{2} }{2}

Donc oui c'est proportionnel.

En espérant t'avoir aidé.